Description of the Life of Karakalpaks in the Period of the Khiva Khanate and the Russian Empire - Turdiev Bakhtiyar Berdikhanovich (Zien Journals, 2022)
The article says that the Karakalpak people, who emigrated from Khorezm after the invasion of Genghis Khan in the XIII century, became the Aral Sea five centuries later. It is also said that the situation of the population has begun to improve with agriculture
Keywords: Karakalpaks; Khorezm; invasion of Genghis Khan